Viability of Methicillin-Resistant Staphylococcus aureus (MRSA) Bacteria Preserved at Different Temperature and Time - Sekar Karima Rachma; Kurniawan; Ikhsan Mujahid; Kurnia Ritma Dhanti (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kuningan, 2024)
The bacteria Staphylococcus aureus, a normal component of human flora, is easily mutated and antibiotic-resistant, leading to the creation of Methicillin-Resistant Staphylococcus aureus (MRSA). This bacterium is a difficult-to-control nosocomial infection in healthcare settings, so it must be stored using specialized preservation agents, like DMSO, to investigate the nature and characteristics of these bacteria for prevention, control, and therapy. The purpose of this study was to evaluate the survival of MRSA bacteria that had been kept in a DMSO solution at various temperatures and periods. This study was carried out between July and October2022 using a one-shot study case research design, data analysis, and quantitative descriptive analysis. According to the findings, MRSA bacteria held in 15% DMSO solution lost viability over time and at various storage temperatures. Among various bacterial species held at various storage temperatures, MRSA bacteria had the lowest colony loss rate (-20 °C). Based on the findings of this study, it can be said that the preservation of MRSA bacteria at freezing temperature (-20 °C) and storage length of one month resulted in the greatest survivability of the bacteria when stored in 15% DMSO solution.